Struktur Komunitas Kupu-kupu (Lepidoptera: Papilionoidea) di Kawasan Resort Sukamade Taman Nasional Meru Betiri dan Pemanfaatannya sebagai Buku Ilmiah Populer - Dimas Amirul Hasan (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Butterflies play an important role in maintaining ecosystem balance, particularly as pollinators and bioindicators. This study was conducted in the Resort Sukamade Area, Taman Nasional Meru Betiri, to analyze the butterfly community structure and morphological similarity relationships using a phenetic approach. This conservation area faces challenges in the form of human activities, forest fires, and changes in vegetation structure that affect habitats and butterfly communities. This study also aims to evaluate the feasibility of a popular scientific book. Sampling was carried out using the sweeping method across four habitat types distributed in 12 research points, resulting in the identification of 26 species from 4 families with a total of 423 individuals. Ypthima horsfieldii showed the highest relative abundance and important value index compared to the other butterfly species recorded in the study area. Open Land exhibited the greatest butterfly diversity (H' = 2,72) and the highest species richness, as indicated by the Margalef index (4,67). In contrast, Coastal Forest showed the highest dominance index (0,17), whereas Closed-canopy Forest demonstrated the highest level of species evenness (0,84). Abiotic factors such as temperature, humidity, wind speed, and light intensity were correlated with certain butterfly species. Multivariate analysis (CCA and PCA) further revealed specific correlations between butterfly distribution and abiotic factors, as well as associations between butterflies and plants. Finally, the popular scientific book developed from this research was declared highly feasible with a validation score of 89,7%.
FINALISASI oleh Arif 2026 Juni 03
Keywords: Butterfly Community Structure; Papilionoidea; Popular Science Book; Sukamade Resort